콩 RIL 집단의 내탈립성 변이 탐색 및 유망계통 선발 - 서정현; Jeong Hyun Seo; 강범규; Beom Kyu Kang; 김현태; Hyun Tae Kim; 김홍식; Hong Sik Kim; 최만수; Man Soo Choi; 오재현; Jae Hyeon Oh; et al. (Korean journal of crop science, 2019)
Pod shattering during the maturing stage causes a serious yield loss in soybean. It is the main limiting factor of soybean cultivation and mechanization. It is important to develop varieties suitable for mechanical harvesting and to develop energy-efficient agricultural machinery to save labor and costs. ‘Daewonkong,’ developed by the National Institute of Crop Science (NICS) in 1997, is an elite cultivar that occupies more than 80% of the soybean cultivation area in Korea because of its strong tolerance to pod shattering. The objectives of this study were to investigate the variation in pod shattering degree in a RIL population developed from a ‘Daewonkong’ parent and to select promising lines with pod shattering tolerance. ‘Daewonkong’ demonstrated a high level of tolerance to pod shattering compared to the ‘Tawonkong’ and ‘Saeolkong’ varieties, with no shattered pods after 72 hours of drying. Screening of pod shattering showed a clear distinction between the tolerant and susceptible varieties. Also, the distribution of shattering pod ratio in the two populations showed a similar pattern for three years. The promising lines with pod shattering tolerance included 27 lines in the ‘Daewonkong’×‘Tawonkong’ population and 21 lines in the ‘Daewonkong’×‘Saeolkong’ population. The promising lines are expected to be widely used as breeding parents for creating soybean cultivars with pod shattering tolerance.